The Basic for Trade According to International Trade Theories and Their Relation with Trade Policies - Jatuliavičienė, Gražina (Ekonomika, 1999)
In the article is presented an overview over some of the competing theories aimed at explaining the basis and gains of international trade. Key classical concepts such as absolute and comparative advantage are explained and extended to include modern-day realities. The article also deals with important new trade theories, which base trade on economies of scale and imperfect competition, as well as on competitive advantage. This leads to the theoretical evaluation of a country’s trade policies and their impact on export performance.